Red Sea circulation during marine isotope stage 5e. (22nd April 2015) - Siccha, Michael; Biton, Eli; Gildor, Hezi
Abstract We have employed a regional Massachusetts Institute of Technology oceanic general circulation model of the Red Sea to investigate its circulation during marine isotope stage (MIS) 5e, the peak of the last interglacial, approximately 125 ka before present. Compared to present‐day conditions, MIS 5e was characterized by higher Northern Hemisphere summer insolation, accompanied by increases in air temperature of more than 2°C and global sea level approximately 8 m higher than today. As a consequence of the increased seasonality, intensified monsoonal conditions with increased winds, rainfall, and humidity in the Red Sea region are evident in speleothem records and supported by model simulations. To assess the dominant factors responsible for the observed changes, we conducted several sensitivity experiments in which the MIS 5 boundary conditions or forcing parameters were used individually. Overall, our model simulation for the last interglacial maximum reconstructs a Red Sea that is colder, less ventilated and probably more oligotrophic than at present day. The largest alteration in Red Sea circulation and properties was found for the simulation of the northward displacement and intensification of the African tropical rain belt during MIS 5e, leading to a notable increase in the fresh water flux into the Red Sea. Such an increase significantly reduced the Red Sea salinity and exchange volume of the Red Sea with the Gulf of Aden. The Red Sea reacted to the MIS 5e insolation forcing by the expected increase in seasonal sea surface temperature amplitude and overall cooling caused by lower temperatures during deep water formation in winter.